Milk and Ayurveda: Unlocking the Secrets of Nutrition, Digestion, and Longevity - Vd Sushant Maksane, Dr.Palak Porwal (South Eastern European Journal of Public Health, 2025)
Milk has been a fundamental part of the human diet for millennia, and in Ayurveda, it is regarded as a vital source of nourishment, health, and longevity. This article explores the multifaceted role of milk in Ayurveda, delving into its numerous health benefits, the different types of milk consumed across society, and the proper ways to consume milk based on Ayurvedic principles. It also highlights the importance of understanding the source, quality, and digestion power of milk to maximize its health benefits. The article emphasizes the critical factors such as the type of cow, buffalo, or goat milk, the proper preparation techniques, and the appropriate time for milk consumption for optimal health. By following Ayurvedic guidelines, milk can be an incredibly potent substance for improving vitality, balancing doshas, and promoting overall well-being..